Clinical characteristics and spectrum of NF1 mutations in 12 unrelated Chinese families with neurofibromatosis type 1 - Bin Mao; Siyu Chen; Xin Chen; Xiumei Yu; Xiaojia Zhai; Tao Yang; Lulu Li; Zheng Wang; Xiuli Zhao; Xue Zhang (BMC, 2018)
Abstract Background Neurofibromatosis type 1 (NF1) is a common autosomal dominant disorder caused by a heterozygous germline mutation in the tumor suppressor gene NF1. Because of the existence of highly homologous pseudogenes, the large size of the gene, and the heterogeneity of mutation types and positions, the detection of variations in NF1 is more difficult than that for an ordinary gene. Methods In this study, we collected samples from 23 patients among 46 study participants from 12 unrelated Chinese families with NF1. We used a combination of Sanger sequencing, targeted next-generation sequencing, and multiplex ligation-dependent probe amplification to identify potential mutations of different types. Results Seven recurrent mutations and four novel mutations were identified with the aforementioned methods, which were subsequently confirmed by either restriction fragment length polymorphism analysis or Sanger sequencing. Truncating mutations accounted for 73% (8/11) of all mutations identified. We also exhaustively investigated the clinical manifestations of NF1 in patients via acquired pathography, photographs and follow-up. However, no clear genotype-phenotype correlation has been found to date. Conclusion In conclusion, the novel mutations identified broaden the spectrum of NF1 mutations in Chinese; however, obvious correlations between genotype and phenotype were not observed in this study.